A Critical Discourse Analysis of a Selection of Thai and American Music Radio Programs in Terms of the Influence of the Language of American Culture on the Language of Thai Culture - Sumanawika Unchit (Yayasan Visi Intan Permata, 2016)
This study is concerned with the main linguistic differences and similarities between the Thai and American DJs’ conversations on the radio and the influence of American culture on Thai culture (in terms of language) as seen in those conversations. There were three radio stations chosen for comparison: SEED 97.5 FM, MET 107 FM, and New York PLJ 95.5 FM. DJs’ conversations are analysed from the perspective of code switching, language appraisal, ecology of language, speech genres, and sociolinguistics. The result show both differences and similarities. Thai and American radio feature different points of view and cultural beliefs. However, the three data samples data also show similarities related to the music content.